The African renaissance and the Afro-Arab spring : a season of rebirth? - Villa-Vicencio, Charles; Doxtader, Erik; Moosa, Ebrahim (Georgetown University Press, 2015)
The hope and despair surrounding the Afro-Arab Spring in North Africa has only begun to be played out in regional and global politics. And the call for an African renaissance that followed the miraculous political transition in South Africa is, twenty years later, viewed with similar ambiguity. What is clear is that current developments in Africa, north and south, promise something markedly different from what has prevailed at any point since the dawn of the African independence movements of the 1950s and 60s. But the continent's own identity remains unresolved, posing the question whether and how its multiple and divergent experiences can be understood and perhaps woven into a basis for unity. Contributors to this volume explore whether or not events north of the Sahara and on the southern tip of Africa can be catalysts for change in other parts of the continent. Chapters assesses the nature of political resistance, revolution, and transition in North and Southern Africa, addressing critical factors--economics, culture, gender, theology--that reveal the promises and perils of African reform. Includes a foreword by former South African president Thabo Mbeki.